2006
DOI: 10.1097/01.ccm.0000239112.49567.bd
|View full text |Cite
|
Sign up to set email alerts
|

Nursing home patients in the intensive care unit: Risk factors for mortality

Abstract: Among vulnerable elderly nursing home residents, higher APACHE III score is independently associated with increased hospital mortality rate and mortality within 90 days. Among hospital survivors, impaired functional status is independently associated with increased mortality rate within 90 days.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 29 publications
0
14
0
Order By: Relevance
“…In nursing home residents discharged from ICU, impaired functional status has been shown to be independently associated with increased mortality [26]. Prior functional status may also have an effect on treatment of patients, as they are more likely to receive do-notresuscitate directives when admitted to ICU [27].…”
Section: Discussionmentioning
confidence: 98%
“…In nursing home residents discharged from ICU, impaired functional status has been shown to be independently associated with increased mortality [26]. Prior functional status may also have an effect on treatment of patients, as they are more likely to receive do-notresuscitate directives when admitted to ICU [27].…”
Section: Discussionmentioning
confidence: 98%
“…The observation is consistent with other studies that have shown mortality rates of 37% to 50% in patients who are discharged from ICUs to either nursing homes or long-term care hospitals. [21][22][23] With further study, these simple definitions may serve as adequate measures for clinical research studies in elderly populations who are using discharge disposition as a primary outcome. …”
Section: Discussionmentioning
confidence: 98%
“…Similarly, in a study aimed at the identification of intensive care unit (icU), admission characteristics predictive of mortality among older nursing home residents, a higher aPacHe iii score (adj-RR 1.02; 95% ci: 1.01-1.04) and increasing functional dependency before icU admission (adj-RR 1.6; 95% ci: 1.05-2.57, per aDL quartile) were independently associated with increased mortality rate within 90 days (26).…”
Section: Discussionmentioning
confidence: 99%